ANALISIS KEPRAKTISAN INSTRUMEN PENILAIAN AUTENTIK MATERI EKOSISTEM DI SMA DITINJAU DARI ASPEK PENGGUNA - Dian Dwi Putri Ulan Sari Patongai; Saparuddin; Sahribulan (Universitas Cokroaminoto Palopo, 2021)
This study aims to analyze the practicality of an authentic assessment instrument for ecosystem materials in high school which has been developed using the 4D development model (Define, Design, Development, Disseminate) by Thiagarajan. The practicality of the instrument in terms of the user aspect is measured using a teacher response questionnaire filled out by the teacher and also students who are given an assessment instrument to use. Aspects assessed in the instrument are related to aspects of clarity and aspects of understanding/acceptance. Practically, teachers find it easy to use it in assessing student learning outcomes and students who feel enthusiastic about learning that apply authentic assessment instruments. From the results of data analysis carried out, the teacher gave a very positive response to both aspects which were assessed with a student response value of 92.5% greater than 85%. Meanwhile, the student response showed that the students gave a positive response to the implementation of authentic assessment of ecosystem materials with a response value of 84.11%. Thus, it can be concluded that the authentic assessment instrument for ecosystem material that has been developed can practically be used properly and gives a positive response from both teachers and students.